2018
DOI: 10.5194/tc-12-3409-2018
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: Impact of the recent atmospheric circulation change in summer on the future surface mass balance of the Greenland Ice Sheet

Abstract: Abstract. Since the 2000s, a change in the atmospheric circulation over the North Atlantic resulting in more frequent blocking events has favoured warmer and sunnier weather conditions over the Greenland Ice Sheet (GrIS) in summer, enhancing the melt increase. This circulation change is not represented by general circulation models (GCMs) of the Coupled Model Intercomparison Project Phase 5 (CMIP5), which do not predict any circulation change for the next century over the North Atlantic. The goal of this study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 32 publications
5
75
0
Order By: Relevance
“…Outputs generated at sub-daily temporal resolution are, then, aver-aged to obtain daily values. We refer to Fettweis et al (2017) for the evaluation of this NCEP/NCARv1 forced simulation and to Delhasse et al (2020) for the list of improvements made since MARv3.5 used in Fettweis et al (2017).…”
Section: 2mentioning
confidence: 99%
“…Outputs generated at sub-daily temporal resolution are, then, aver-aged to obtain daily values. We refer to Fettweis et al (2017) for the evaluation of this NCEP/NCARv1 forced simulation and to Delhasse et al (2020) for the list of improvements made since MARv3.5 used in Fettweis et al (2017).…”
Section: 2mentioning
confidence: 99%
“…High pressure conditions are further linked to GrIS warming trends since the mid-1990s (Box et al 2012;Ding et al 2014;Fettweis et al 2013b) and record-breaking melt in recent summers (Hanna et al 2014;McLeod and Mote 2016;Tedesco et al 2013Tedesco et al , 2016. Having significantly increased since 1981 (Hanna et al 2016), summertime Greenland blocking is expected to remain an important driver of extreme melt throughout the twentyfirst century (Delhasse et al 2018;Hahn et al 2018;Hanna et al 2018;Hofer et al 2019). Predictions of Greenland melt therefore depend on understanding the impacts of blocking, with potential global effects on sea level rise (Aschwanden et al 2019;Fettweis et al 2013a;Shepherd et al 2012) and ocean circulation changes (Böning et al 2016;Oltmanns et al 2018;Rahmstorf et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Their highest Greenland SLE projection (0.17 m by 2100) was found when the ice-sheet model was forced by canESM2 RCP8.5 simulation results. However, using also a subset of CMIP5 models (including canESM2) and comparing with reanalysis, Delhasse et al (2018) [93] have shown that some changes observed over the last two decades in atmospheric circulation (i.e., increase in blocking high frequencies in summer) could not be reproduced by the CMIP5 models. They further concluded that, if the current summer atmospheric circulation pattern over Greenland happens to persist, projected Greenland SMB contribution to sea-level rise could be amplified by a factor of two for a similar temperature increase.…”
Section: Barystatic-grd Componentsmentioning
confidence: 99%
“…They further concluded that, if the current summer atmospheric circulation pattern over Greenland happens to persist, projected Greenland SMB contribution to sea-level rise could be amplified by a factor of two for a similar temperature increase. Therefore, we build our high-end B scenario by considering that the largest model projection found in Fürst et al (2015) [92] could be amplified by a factor two following the arguments of Delhasse et al (2018) [93]; this would lead to a Greenland SLE of 0.34 m by 2100. Note that the most recent expert elicitations on ice-sheet contribution suggested an upper bound of the likely range at 60 cm [73], which gives us confidence that our high-end B Greenland component projection remains credible.…”
Section: Barystatic-grd Componentsmentioning
confidence: 99%